Boriding kinetics of C35 steel: estimation of boron activation energy and the mass gain. Issue 2 (23rd April 2014) - Bouarour, B.; Keddam, M.; Allaoui, O.; Azouani, O.
Abstract : The present work is concerned with the determination of boron activation energy in the C35 steel and an estimation of the mass gain generated by the boriding treatment. The boride layers are produced by the pack-boriding method on the C35 steel in the temperature range of 800−1000 °C for a treatment time ranging from 0.5 to 8 h. The presence of both FeB and Fe2 B phases was confirmed by the X-ray diffraction technique and by a microscopic examination of the cross-sections of borided samples. The boron activation energy was evaluated as 153.1 kJ mol -1 in the temperature range of 800−1000 °C. This value of energy is in agreement with the literature data. The mass gain was measured by weighing the samples before and after the boriding treatment by the weighing technique. The evolution of mass gain as a function of temperature and time can be described by a parabolic law. Finally, an iso-thickness diagram was established to be used as a tool to optimize the boride layers thicknesses according to the industrial application.